En Retrospectiva. La Danza… Historia De Vida De Oscar Javier González Páez, A Modo De Relato Biográfico, En El Departamento De Cundinamarca. - González Páez, Oscar Javier (Universidad Antonio Nariño, 2022)
In Retrospective Dancing... Oscar Javier González Páez’s life story, as a biographical account, in the Department of Cundinamarca, has a qualitative approach. It describes his role as a researcher, the techniques and elements he took into account for his story; secondly, it describes his origins and mentions how he began his dancing teaching process in elementary schools, where he taught children in an empirical way. The third aspect, relates the process as a director in independent cultural organizations and his role as director of dance training schools in the Department of Cundinamarca.